The specifics of building a sports management system in the Russian Federation and other countries - Viter K.A.; Samokhina E.A.; Marion L.S.; Yesina O.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study – is to determine the specifics of the management structure in the sports industry both in Russia and in other countries. Methods and structure of the study. As part of the research methodology, a comparative analysis of sports management systems in Russia and abroad was performed, based on a review of relevant scientific publications. Results and conclusions. The results of the work demonstrate significant differences in approaches to sports management between foreign countries and the Russian Federation. These differences primarily relate to the level of government involvement in the management and supervision of programs aimed at the development of mass sports and physical education, as well as differences in the ways of financing sports events.